2017
DOI: 10.1002/elps.201600478
|View full text |Cite
|
Sign up to set email alerts
|

Improved separation and size characterization of gold nanoparticles through a novel capillary zone electrophoresis method using poly(sodium4‐styrenesulfonate) as stabiliser and a stepwise field strength gradient

Abstract: A novel capillary zone electrophoresis (CZE) method was developed for an improved separation and size characterization of pristine gold nanoparticles (AuNP) using uncoated fused-silica capillaries with UV-Vis detection at 520 nm. To avoid colloid aggregation and/or adsorption during runs, poly(sodium 4-styrenesulfonate) (PSS) was added (1%, w/v) in the running buffer (CAPS 10 mM, pH 11). This polyelectrolyte conferred an enhanced stabilization to AuNP, both steric and electrostatic, exalting at the same time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…For example, poly(4-styrenesulfonate) (PSS) was studied as an alternative to SDS for improved separation and size determination of AuNPs. 71 The addition of PSS along with a stepwise field gradient significantly improved the resolution for AuNPs with diameters ranging from 5 to 20 nm. Similar observations were made for stabilizers such as Pluronic F-127, citrate, and cetyltrimethylammonium allowing differences in AuNP surface chemistry and size to be revealed.…”
Section: Applicationsmentioning
confidence: 99%
“…For example, poly(4-styrenesulfonate) (PSS) was studied as an alternative to SDS for improved separation and size determination of AuNPs. 71 The addition of PSS along with a stepwise field gradient significantly improved the resolution for AuNPs with diameters ranging from 5 to 20 nm. Similar observations were made for stabilizers such as Pluronic F-127, citrate, and cetyltrimethylammonium allowing differences in AuNP surface chemistry and size to be revealed.…”
Section: Applicationsmentioning
confidence: 99%
“…It is reported that a cluster of Au nanoparticles in different average diameters has been resolved by CZE. 24 Therefore, the resolution of the CND clusters by the MEKC format suggests that the adsorption property of dodecyl sulfate ion (DS − ) to CNDs would similarly be categorized into two or four groups. The migration time of the apparently anionic CNDs, however, slightly shifted from the migration time of the EOF.…”
Section: Surfactant Assisted Capillary Zone Electrophoresis Of Cndmentioning
confidence: 99%
“…The technique has the advantages of rapidity, high resolving power, ultrasmall sample, and reagent consumed and considerable simplicity in operation. Combined with different detection techniques, such as UV-vis detection, electrochemical detection (ED), fluorescence detection, MS, chemiluminescence detection (CL), and electrochemiluminescence detection (ECL) [1][2][3], CE can meet many kinds of specific requirements and has been applied to determine a great variety of analytes [4][5][6][7][8]. Moreover, the relative simplicity of the instrumental design makes CE suitable to be miniaturized to MCE, which, introduced by Manz et al [9], changes the way of CE analysis due to its portability and high degree of integration that allows sample handling, reaction, injection, separation, and detection to be performed in a chip [10][11][12].…”
Section: Introductionmentioning
confidence: 99%